Mathematical Problem Solving Ability Reviewed from Habits of Mind Through Problem Based Learning Model Assisted with Wordwall Education Game - Laviona, Zuny; Amidi, Amidi (Universitas Negeri Semarang, 2024)
This study aims to test the effectiveness of the Problem Based Learning model assisted by Wordwall Education Game and describe mathematical problem solving skills when viewed from habits of mind. The research method used is a mixed method with the sequential explanatory model. The research population was all students of class VII of SMP Negeri 22 Semarang, the research samples were class VII G as the experimental class and VII H as the control class. The research subjects were students of class VII SMP N 22 Semarang consisting of 2 students based on each level of habits of mind. The results showed that the Problem Based Learning model assisted by Wordwall Education Game was effective on mathematical problem solving ability, namely students in the experimental class could achieve learning completeness, mathematical problem solving ability in the experimental class was better than the control class, and the proportion of students in the experimental class was better than the control class. Then the qualitative description shows that students who have a high level of habits of mind can fulfill all indicators of mathematical problem solving ability, students with a moderate level of habits of mind fulfill 3 indicators of mathematical problem solving ability, and students who have a low level of habits of mind do not fulfill all indicators of mathematical problem solving ability.